ANALISIS KEMAMPUAN METAKOGNISI SISWA SMP PADA MATERI SEGITIGA - Widya Marliana; Indrie Noor Aini (IKIP Siliwangi, 2021)
This study aims to describe and analyze the metacognition attainment of junior high school students when solving math problems on triangular material. The research was conducted using descriptive qualitative methods. The research subjects consisted of 3 students of class VIII at one of the junior high schools in Bekasi Regency, each of whom had high, medium and low math abilities. Data were collected by means of 1 test question representing all indicators of metacognition ability. Data were analyzed by giving a score on each subject's answer, then the score was converted into a percentage value. The test results were analyzed based on indicators of the ability of metacognition is Awareness, Regulation, and Evaluation. The results showed that students with high mathematical ability (ST) had metacognition attainment of 75%, students with moderate mathematical ability (SS) had metacognition achievement of 25%, and students with low mathematical abilities (SR) had metacognition achievement of 12.5%. Students with moderate math abilities (SS) and students with low math abilities (SR) have not used metacognition abilities to the maximum.